Metaphorical conceptualization in national sports - Fedorova Claudia; Argounov Vasily (SHS Web of Conferences, 2022)
The article addresses a number of issues in the study of conceptual metaphors related to their nature, typology, and functioning in various discourses. Metaphorical conceptualization on the material of the Yakut language has not so far been systematically explored in the cognitive linguistics literature on metaphor. On the basis of the theoretical framework of conceptual metaphor theory, the paper analyses creative and frozen metaphors and their systematic interconnection during conceptualization in sports discourse. The basic metaphor of sports discourse SPORT IS WAR is frequently elaborated by metaphorical nominations, such as “bootur” (ancient Yakut warriors), “soldaty” (soldiers), etc. In national sports, conceptual metaphors vividly and expressively reflect the specificity of not only the language, but also the history, traditions, and the metaphorical conceptualization of a particular ethnos.